Bitcoin and Stock Market Return Correlation: A Sectoral Analysis of the S&P500 - Narouz, Michael (AUC Knowledge Fountain, 2024)
This thesis studies the correlation between Bitcoin returns and stock market price returns for the S&P500 US stock market index by dividing the index into 11 sectors based on the industry and checking for correlation between Bitcoin returns and the returns of the stocks in each sector individually. The GARCH model is used due to its ability to account for the empirical phenomenon of volatility clustering that is usually present in financial time series datasets such as those used in this thesis. The results show statistically significant positive correlation between Bitcoin returns and stock market returns for all 11 sectors, indicating Bitcoin does not act as a hedge against any of the sectors of the S&P500 when each sector is considered individually. The results of this paper are of value to both policymakers and investors as this segregation of the S&P500 to determine correlation with cryptocurrency returns has not been attempted in previous research. The results would specifically be of benefit to investors who are overweight in one of the 11 sectors of the S&P500.